Factors affecting Menstrual Hygiene Management Practices among Women Visiting a University Hospital of Lahore: A Cross-Sectional Study: Menstrual Hygiene Management Practices among Women - Janjua, Mahham; Wajid, Rabia; Haider, Shazia; Sehgal, Shazia; Amir, Nayab; Malik, Kiren Khurshid (Pakistan Journal of Health Sciences, 2025)
Menstrual practices are considered taboo in various spheres of our lives, serving as an impediment to the provision of adequate resources to women. Objective: To determine factors affecting menstrual hygiene practice (MHMP) in the population visiting a Tertiary Care Hospital. Methods: A Quantitative descriptive study was conducted at Lady Willingdon Hospital from July to December 2024. 382 female were included in the study after seeking informed consent and approval from ERB. The inclusion criteria for this study were female aged 18-45 years with regular menstrual cycles. Female who were pregnant or with irregular menstrual cycles were excluded. The data were analyzed by using SPSS version 21.0. Results: In this study age significantly influenced hygiene practices, with younger females (12-17 years) more likely to engage in unsafe practices (p=0.005). Maternal secondary education was a key factor in promoting safe hygiene practices (p=0.009). Awareness about menarches and the primary source of information were strongly associated with better hygiene practices (p<0.001). Sanitary pad usage was prevalent (99%) and linked to safer practices (p = 0.0032), while access to water and sanitation facilities improved hygiene (p=0.005). Conclusions: This study highlights the crucial role of socio-demographic factors and access to sanitation facilities in influencing menstrual hygiene management practices. Promoting education, increasing awareness, and improving access to sanitary products and sanitation facilities are essential to enhance safe menstrual hygiene practices.